Preying on the State : The Transformation of Bulgaria after 1989 - Ganev, Venelin I. (Book collections on Project MUSE., 2007)
Immediately after 1989, newly emerging polities in Eastern Europe had to contend with an overbearing and dominant legacy: the Soviet model of the state. At that time, the strength of the state looked like a massive obstacle to change; less than a decade later, the state's dominant characteristic was no longer its overweening powerfulness, but rather its utter decrepitude. Consequently, the role of the central state in managing economies, providing social services, and maintaining infrastructure came into question. Focusing on his native Bulgaria, Venelin I. Ganev explores in fine-grained detail the weakening of the central state in post-Soviet Eastern Europe. Ganev starts with the structural characteristics of the Soviet satellites, and in particular the forms of elite agency favored in the socialist party-state. As state socialism collapsed, Ganev demonstrates, its institutional legacy presented functionaries who had become accustomed to power with a matrix of opportunities and constraints. In order to maximize their advantage under such conditions, these elites did not need a robust state apparatus-in fact, all of the incentives under postsocialism pushed them to subvert the infrastructure of governance. Throughout Preying on the State, Ganev argues that the causes of state malfunctioning go much deeper than the policy preferences of "free marketeers" who deliberately dismantled the state. He systematically analyzes the multiple dimensions, implications, and significance of the institutional and social processes that transformed the organizational basis of effective governance.